English Literature Study Program Student’s Anxiety in Discussion Activity of Learning Modern Cultural Studies at Universitas Bumigora - Hastuti, Hilda; Supatmiwati, Diah; Dewi, Puspita; Rahmawati, Lela (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This research was carried out to investigate students’ anxiety in group discussion of learning modern cultural studies at Universitas Bumigora. It’s used to identify whether factors that may contribute to anxiety in learning of modern cultural studies based on students’ perspectives. The method used in this research is qualitative with case study approach seventeen anxious students were chosen as participants. The data gained by using observation and mediated interview. The result of this research showed that speaking or expressed opinion by using English via audio or camera of video on, incomprehensible input, lack of reading, students’ beliefs of learning modern cultural studies, and lack of preparation were the five factors that are able to contribute to the students’ anxiety in discussion activity of learning modern cultural studies